SISTEM PENGENDALIAN JARAK TERBANG PADA PESAWAT QUADCOPTER UNTUK MENGHINDARI LOSS OF CONTROL - Agus Basukesti; Yuliani Indrianingsih (Teknoin, 2014)
This research is to uncover the events spiral out of control ( out of control ) that often occurs at the plane quadcopter causing loss or damage. The importance of taking this topic because the results of the research will be of great benefit in the development of microelectronic technology , especially for the design of UAV aircraft in Indonesia. Sequence starting from designing the study continued until the plane quadcopter flight test. Reliability and accuracy control flying distance flight test conducted and supported by the increase in equipment and repair kirnerja control algorithm. Success of the flight test aircraft reliability and security, determined on setting position effective control distance . Most aircraft can not transmit information if the aircraft in unsafe conditions distance position .  Benefits and the subsequent development of this quadcopter eg sensor system to detect and send the data somewhere air conditions can be developed. For aerial photography at an affordable cost while the control plane algorithms can be applied to steer the rocket to the right targets. Thus the results of the design and control algorithms on the plane quadcopter distance is very useful for science and the general public.